Non-utilization of Postnatal Care Services and Related Factors among Women in Osun State, Nigeria. - Olajubu, Aanuoluwapo Omobolanle (Journal of Midwifery & Reproductive Health, 2021)
Background & aim: Utilization of postnatal care (PNC) services has not been optimal in many low- and medium-income countries despite the importance and benefits associated with it. Hence, this study was conducted to determine the prevalence of PNC non-utilization and its related factors among women in Osun State, Nigeria. Methods: This study adopted a descriptive cross-sectional design involving 380 women attending antenatal clinic at the primary health centers, using a multistage sampling technique. A structured questionnaire was used to obtain data which was analyzed using descriptive and inferential statistics. The IBM SPSS statistics version 20 was used. Results: About three-quarter (75.8%) of the respondents did not attend PNC services and 62.4% did not know the importance of attending PNC services. From multivariate analysis, six variables emerged as predictors of PNC non-utilization i.e. women with no health issues (OR: 7.57, 95% CI: 3.02-18.98), being in the age group 31 years and above (OR: 2.35, 95% CI: 1.21-4.58), no formal PNC clinic appointment (OR: 2.09, 95% CI: 1.13-3.87), lower income (OR: 1.97, 95% CI: 1.10-3.56), lower parity (OR: 1.96, 95% CI: 1.04-3.71) and lack of knowledge of importance of PNC (OR:1.94, 95% CI: 1.06 - 3.56). Conclusion: There is a high level of non-utilization of PNC services among respondents. To increase the uptake of PNC services in Nigeria and improve mother and child health outcomes, public health programs should focus on educating women and significant others on the importance of PNC for mother and newborn.